Hero [videorecording (DVD)] - Tan, Dun, 1957- (Miramax Home Entertainment, 2002)
Long ago, China was divided into seven kingdoms all fighting for supremacy. The King of Qin was most determined to become the first emperor of China. Though many tried to assassinate him, only three inspired fear. The King promised endless wealth and power to anyone who defeats his would-be murderers. No results come until ten years later, when a man called Nameless brought the weapons of the three assassins to the Qin King's palace. Nameless claimed to be an expert swordsman who had defeated all three warriors and had to tell his story to the King.